The Effect of Service Quality and Price on Consumer Satisfaction at Ayam Penyet Ria Restaurant on Jl. Jendral Sudirman Pekanbaru - Andriani, Dessy; Suryatunnisak, Suryatunnisak; Yurnal, Yurnal (First Ciera Publisher, 2024)
The purpose of this study was to determine the effect of service quality and price on customer satisfaction at Ayam Penyet Ria Restaurant, Jl. Jendral. Sudirman Pekanbaru. The sample in this study was 100 consumers. Data analysis used was validity test, reliability test, classical assumption test, multiple linear regression, hypothesis test and determination coefficient test. Based on the results of the study, it is known that through partial test (t-test) there is a significant effect of service quality on customer satisfaction with the test results known t count (2.048) > t table (1.984) and Sig. (0.000) < 0.05. There is a significant effect of price on customer satisfaction with the test results known t count (3.724) > t table (1.984) and Sig. (0.000) < 0.05. Simultaneously shows that service quality (X1) and price (X2) together affect customer satisfaction at Ayam Penyet Ria Jl. Jendral. Sudirman Pekanbaru with the test results known Fcount (324.507) > Ftable (3.09) with a significance of 0.000 < 0.05. In terms of the determination coefficient, the service quality and price variables have an influence of 87.3% on consumer satisfaction while the remaining 12.7% is explained by other factors not studied by the author.